Terasirane pokrajine Ob sedemdesetletnici Geografskega inštituta Antona Melika ZRC SAZU - Kladnik, Drago (ZRC SAZU, Založba ZRC, 2016)
Terraced landscapes with agricultural terraces are cultural landscapes with a special value. This volume presents them in pictures and words in all their diversity and attractiveness. After discussing the global and European dimensions of terraced landscapes and their agricultural terraces, the volume focuses on Slovenian terraced landscapes~they are discussed separately by landscape types, individual regions, and sample cases in the territory of selected settlements (pilot areas). The conclusion also draws attention to the exceptional value and appeal of non-agricultural terraced landscapes that have been shaped by nature and man.